CHINESE OUTBOUND TOURISM: NEW CHALLENGES FOR EUROPEAN TOURISM - Rosario Andreu; Enrique Claver; Diego Quer (Enlightening Tourism: A Pathmaking Journal)
The growth of China’s outbound tourism is a source of both threats and opportunities for European countries. Therefore, European tourism institutions and companies should focus their attention on this emerging market. The objective of this paper is to analyze the consequences that the boom in Chinese tourism could have for European tourism. A critical analysis provides the basis for actions and measures that the main European tourism institutions and companies should adopt in order to face these new challenges.